The Association between Coronary Artery Disease and Hypertriglyceridemia in Libyan Adults: A Cross-Sectional Study - Razk Abdalgwad,; Balha, Ahmed; Fadhlullah, Ali (AlQalam Journal of Medical and Applied Sciences, 2021)
Background and aims. Hypertriglyceridemia is increasingly prevalent multifactorial disease and one of the leading causes of coronary artery disease (CAD). We aimed to explore the relationship between the development of CAD and hypertriglyceridemia in Libyan adults. Methods. A retrospective cross-sectional study was conducted in a cohort of Libyan adults diagnosed with CAD. Participants were divided into groups with high and normal serum triglycerides levels. The likelihood occurrence of CAD in patients with hypertriglyceridemia was determined by using the Bayesian one sample test. Results. In general, 97 patients with established CAD were eligible for this study. 81 (83.5%) had elevated serum triglyceride levels as compared to only 16 (16.5%) with normal serum triglyceride levels, respectively. The mean age of the entire cohort was 60 ± 11.89 years. 53 (54.6%) of patients were females, and 44 (45.4%) were males in the entire cohort, respectively. Hypertriglyceridemia was significantly associated with CAD development. Conclusion. Amongst a cohort of Libyan patients with established CAD, we have found that there was a significant association between the occurrence of CAD and hypertriglyceridemia.